Determinants of commercial banks profitability through analysis of financial performance indicators: evidence from Kosovo - Nuhiu, Artor; Hoti, Arbër; Bektashi, Mejdi (Business: Theory and Practice, 2017)
The purpose of this study is to elaborate whether the determinants of commercial banks’ profitability affect the financial performance of commercial banks in Kosovo. Performance evaluation of commercial banks in Kosovo is done through measurement of financial performance indicators such as Return on Average Equity (ROAE), Return on Average Assets (ROAA) and Net Interest Margin (NIM). The study identifies the main factors that affect the profitability of commercial banks through analysis of financial time series and panel data of the banking sector in Kosovo. The study presents three models of financial performance analysis which highlight the influencing factors. The models are based on regression analysis, and the obtained results emphasize the relationship between the determinant factors of commercial banks profitability expressed through analysis of financial performance indicators. The study concludes that commercial banks profitability in Kosovo is driven mainly by internal determinant factors such as capital adequacy, asset quality and management efficiency, while macroeconomic factors have insignificant impact on financial performance of commercial banks.